دور البرلمان في محاكمة رئيس الدولة: دراسة مقارنة - عمار علي محمد (PROSPECTIVE RESEARCHES, 2023)
The rights، freedoms and public interests of the country are among the most important issues concerned with. For the sake of achieving them the supreme authorities in the state are granted powers that work to serve these interests and achieve goals, Therefore، the responsibility is based on the status, and power granted to the occupants of these positions because the violations committed by these groups affect the state’s sovereignty and prestige and the rights of all citizens and are considered a betrayal of trust and an abuse of power. The president is still in dictatorial and tyrannical regimes not responsible or liable in a fictitious manner, and he cannot be prosecuted, unlike democratic systems that have established constitutional texts and legal rules in which the cases the trial takes place and their procedures are indicated in addition to the sanctions imposed on the head of state in case of conviction.